A bibliometric analysis of the studies in 2019 and 2020 on positive organizational behavior - KurÅŸunmaden, Fatih Ä°brahim; BedÃ¼k, Aykut (JBFEM, 2023)
The actions of individuals in organizations and the factors in the emergence of these actions are evaluated in a scientific framework within the concept of organizational behavior. The concepts of workplace friendship and work dedication, which are concepts that try to reveal the ideas that will positively affect the actions of the individuals in the organization, are included in the scope of the study. Workplace friendship is expressed as informal human interactions in the workplace. On the other hand, work engagement is the dedication of employees to fulfilling their job roles, physically, cognitively and emotionally. The aim of the research is to examine the studies on positive organizational behavior in the literature in 2019 and 2020, when the COVID-19 epidemic was intense. For this purpose, bibliometric analysis method was used in the study. In the study, 261 articles in 2019 and 332 articles in 2020 were included in the scope of the Scopus database. The studies included in the research were examined in accordance with the criteria of author, university, country, method, number of pages, keywords and number of references used. It is thought that the findings obtained as a result of the study will be interpreted and it will provide convenience to the researchers in future studies.